Relações entre a assembleia de peixes e a biomassa, riqueza de espécies e diversidade funcional de macrófitas aquáticas. - Costa, Isadora Cristina Bianchi (2023)
The aquatic macrophytes are considered an essential component of freshwater ecosystems, influencing the structure of fish assemblage that use macrophyte stands in search of food resources and refuge. These plants affect the fish trophic interaction, reducing the competition and predation pressure between the organisms. The goal of this study was to evaluate the relationship between biomass, richness and functional diversity of aquatic macrophytes and theabundance, richness and fish size that use plants as habitat. Fish and macrophytes were sampled in the drought period, in 30 macrophytes stands along a 13.7 km long stretch in the Baía river, located in the Upper Paraná River floodplain. The fish were captured using plexiglass, and the macrophytes were sampled using a square. The relationship between the abundance and richness of fish and the biomass, functional diversity and richness of macrophytes was tested using a generalized linear model (GLM). The relationship between the size of individuals and the biomass of plants was tested using a linear mixed model (LMM). Were captured 25 fish species, totaling 4648 individuals, and 18 macrophytes species. Our results indicate that abundance and richness of fish responded negatively to plant biomass and showed a positive trend in relation to macrophyte richness. However, significant values were verified only in the relationship between abundance of fish and plant biomass, which indicated that this variable may respond better to these changes compared to fish richness. The relationship between macrophyte functional diversity and abundance of fish, showed a significant non-linear response,confirmed bysignificance value, obtained throughathird-orderpolynomial model,being higher in intermediate values of functional diversity, which is associated with greater structuring provided by plants alongofthe gradient.The total length of fish decreased as plant biomass increased, which indicates that the small interstitial spaces in habitats with high macrophyte biomass can restrict the body size of fish, affecting their movement. These results suggest that biomass and functional diversity of macrophytes can influence fish assemblage, as abundance decreases in more complex stands and increases in stands with intermediate functional diversity. The body size of fish also decreases in places with higher plant biomass. Theresults show that macrophytes can structure an environment, modifying the compositionof fish assemblages, and even being able to select characteristics of these animals according to structural complexity.The plantbiomassinfluencesthe abundance and the body size of fishes, reducingthe significant roleofmacrophytes intheformation andselection of aquatic habitats.Thus, this study emphasizes the importance ofpreservationofaquatic macrophytes,protectingthe biodiversity of freshwater ecosystems.